Micrometry of buffalo oocytes recovered from different size of ovarian follicles - NAIK, V S; DEOPURKAR, V I; GULAWANE, S U (The Indian Journal of Animal Reproduction, 2023)
The oocyte diameters were co-related with the follicular size and the quality of oocytes recovered. The oocytes diameter collected from follicle size 3-5 mm and >5 mm were 152.24 μm and 159.6 μm. The percentage of culturable oocytes obtained from >5mm follicle size were higher as compared to follicle size of 3-5 mm. A positive co-relationship was observed between the oocytes diameter, follicle size and culturable oocytes recovered from buffalo ovarian follicles.